Creating effective digital promotion and sales channels in B2C, case of Beeline Kazakhstan - Meirmanov, D. (International School of Economics KAZGUU, Nur-Sultan, 2022)
This study is designed to study the effectiveness of digital promotion and building sales channels in the field of B2C. Beeline Kazakhstan was chosen as an example for the study. During the study of digital promotion channels, it was found out how they differ from traditional channels, how they are used, how effective they are and what are their advantages. The results of the study should help B2C business owners and marketers involved in the promotion of companies in this field in improving the efficiency of using various marketing tools. The dissertation consists of an introduction, a review of the literature, an analysis of the data obtained during the study and a conclusion. The work also includes 3 tables and 4 diagrams
Keywords: digital promotion, sales channels in B2C, Beeline Kazakhstan